2023
DOI: 10.1158/1055-9965.epi-23-0309
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Proteome Association Studies of Breast, Prostate, Ovarian, and Endometrial Cancers Implicate Plasma Protein Regulation in Cancer Susceptibility

Abstract: Background: Predicting protein levels from genotypes for proteome-wide association studies (PWAS) may provide insight to the mechanisms underlying cancer susceptibility. Methods: We performed PWAS of breast, endometrial, ovarian, and prostate cancers and their subtypes in several large European ancestry discovery consortia (effective sample size: 237,483 cases/317,006 controls) and tested the results for replication in an independent European ancestry GWAS (31,969 cases/410,350 controls). We performed PWAS usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…This disruption of cellular homeostasis contributes to the initiation and progression of tumorigenesis, particularly in the context of leukemia ( 30 ). A recent proteome association study has further confirmed the association between SNUPN and breast cancer, which was in consistent with our finding ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…This disruption of cellular homeostasis contributes to the initiation and progression of tumorigenesis, particularly in the context of leukemia ( 30 ). A recent proteome association study has further confirmed the association between SNUPN and breast cancer, which was in consistent with our finding ( 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…Recent advancements in molecular technologies and techniques have shown significant potential in utilizing plasma protein biomarkers such as Adipsin and CA15-3 for early detection and quantification for diagnostic and therapeutic applications in breast cancer ( Afzal et al, 2022 ; Rajkumar et al, 2022 ; Veyssière et al, 2022 ). A recent high-throughput study identified 61 proteins associated with various cancers ( Gregga et al, 2023 ). While this study provided valuable insights into pan-cancer associations, it did not explore causation.…”
Section: Discussionmentioning
confidence: 99%